Natesa - Temples of India Project Team (Jio Institute, 2024)
The panel depicting Shiva in his dancing form, Natesa, might have once adorned the ceiling of a lost Shaiva temple on Harsha Hill. Even though Natesa is not typically depicted as an independent sculpture in Rajasthan temples, he often appears as an important figure in the architectural spaces. He is elegantly portrayed above the doorway of the main temple at Baroli and elsewhere at Nilakantha and the later Chauhan Temple at Adhai Din Ka Jhonpra. Natesa is surrounded by various dancers and musicians. He is gracefully holding ḍamru in his right hand and possibly a trident in his left hand, which is significantly damaged. Tightly cloistered figures of dancers and musicians in action and angular postures not only provide visual centrality to the figure of dancing Natesa but also enhance the rhythmicity of the scene. To his immediate left is a musician holding a pakjavaja-like drum. The instrument occupies a central position in the squarish space created between Natesa and a dancer on the sides and between the face of the drummer and the dwarf at the bottom